서스펜션 시스템 및 컨트롤러 - YAMASHITA MIKIO (2024)
서스펜션 시스템은, 차체와 차륜의 상대 이동에 의해 통로 내에 생기는 작동 유체의 유통을 감쇠력 가변 액추에이터에 의해 조정하여, 소프트한 특성으로부터 하드한 특성까지 감쇠력을 조정 가능한 가변 댐퍼와, 감쇠력 가변 액추에이터를 제어하는 컨트롤러를 구비한다. 가변 댐퍼는, 특정 주파수의 진동에 대하여 감쇠력을 저감하는 주파수 감응부를 더 갖고 있다. 컨트롤러는, 차체와 차륜의 상대 이동의 주파수가 주파수 감응부에 설정된 제1 주파수보다 낮은 경우에, 감쇠력을 목표 감쇠력으로 제어할 때의 소프트측으로부터 하드측으로의 변화율을 크게 한다. A suspension system includes: a variable damper configured to use a damping force variable actuator to adjust communication of working fluid generated in a passage by a relative movement between a vehicle body and a wheel, to thereby adjust a damping force over a range of a soft characteristic to a hard characteristic; and a controller configured to control the damping force variable actuator. The variable damper further includes a frequency response unit configured to reduce the damping force for vibration at a specific frequency. The controller is configured to increase a change rate from a soft side to a hard side at a time of controlling the damping force to reach a target damping force when a frequency of the relative movement between the vehicle body and the wheel is lower than a first frequency set to the frequency response unit.